التمويل بالصكوك الاسلامية وفق مقاربة محاسبية - حشمان ،سرين; حدبي، عبد القادر (جامعة الوادي University of Eloued, 2025)
The study aims to highlight the accounting treatment of Islamic sukuk according to the accounting standards issued by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI), particularly Standards No. 33 and 34, which cover investments in sukuk, stocks, and similar instruments, as well as sukuk reporting. The focus is on the principles of classification, recognition, measurement, presentation, and disclosure of sukuk investments, as well as the requirements for preparing financial statements for sukuk assets. The study concludes that Islamic sukuk are an innovative financial product requiring special accounting treatment distinct from conventional bonds, with specific standards considering the principle of profit and loss sharing. The findings also offer an accounting approach for the emerging sukuk market in Algeria.
An Accounting Approach for Islamic Sukuk financing
Keywords: الشركة ذات الغرض الخاص; الصك; Sukuk; Special purpose Vehicle; AAOIFI